(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Digital transformation becomes a significant driver for numerous industries such as sports, food services, automobiles, and clothing. Firms are obliged to understand how to develop digital capabilities to avoid an inevitable technological disruption and transform their business model successfully. The notion of digital transformation for Sports Organizations in Thailand is a novel idea in academia. This research aims to explore an insight of Sport Organization in Thailand. It focuses on what dimensions should be considered and incorporated while implementing any digital transformation. This research inductively builds a digital transformation framework for sports organizations in Thailand via reviews and in-depth interviews of 28 experts with a digital and sporting background.This research agenda proposes a framework driven by–1) reviewing digital transformation literature and the work on digital maturity concepts on a theoretical basis, 2) proposing and refining a conceptual model from the experts’ critical insights. Furthermore, research findings indicate that digital transformation for Sports Organizations in Thailand should incorporate six capability dimensions composing of strategy, agility(organization and culture), operations(including sports sponsors and sporting agencies), people (employees), technology, and sports fans/consumers when considering such an implementation. Such capabilities should be viewed as an important basis for a research initiative in digital transformation in Thailand’s sports organizations. Practitioners can modify or adapt the proposed conceptualization model and the defined six capability dimensions as guidance for the current state and progress of their digital transformation efforts